2021
DOI: 10.3390/molecules26227006
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cellulose Derivatives Containing Metal (Cu, Fe, Ni) Oxide Nanoparticles as Eco-Friendly Corrosion Inhibitors for C-Steel in Acidic Chloride Solutions

Abstract: Novel environmentally-friendly corrosion inhibitors based on primary aminated modified cellulose (PAC) containing nano-oxide of some metals (MONPs), for instance iron oxide nanoparticles (Fe3O4NPs), copper oxide nanoparticles (CuONPs), and nickel oxide nanoparticles (NiONPs), were successfully synthesized. The as-prepared PAC/MONPs nanocomposites were categorized using Fourier transform infrared spectroscopy (FT-IR), transmission electron microscope (TEM), field-emission scanning electron microscopy (FE-SEM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…The properties of cellulose, such as film-forming, adhesion, high mechanical strength, and high susceptibility to functionalization and chemical modification, have drawn interest in it This journal is © the Owner Societies 2024 as a possible polymer matrix for anticorrosive coatings. 51,52 The type of cellulose used, the composition of the coating, and the particular environmental conditions to which the coatings are exposed are some factors that affect cellulose's corrosion protection performance. Further developments in cellulosebased anticorrosive coatings are anticipated as this field's research and development continue, which could result in wider industrial adoption of these coatings across various industries.…”
Section: What Makes Cellulose and Its Derivatives Effective Corrosion...mentioning
confidence: 99%
“…The properties of cellulose, such as film-forming, adhesion, high mechanical strength, and high susceptibility to functionalization and chemical modification, have drawn interest in it This journal is © the Owner Societies 2024 as a possible polymer matrix for anticorrosive coatings. 51,52 The type of cellulose used, the composition of the coating, and the particular environmental conditions to which the coatings are exposed are some factors that affect cellulose's corrosion protection performance. Further developments in cellulosebased anticorrosive coatings are anticipated as this field's research and development continue, which could result in wider industrial adoption of these coatings across various industries.…”
Section: What Makes Cellulose and Its Derivatives Effective Corrosion...mentioning
confidence: 99%
“…Similarly, incorporating nano-oxides of various metals (MONPs), such as CuONPs, Fe 3 O 4 NPs, and NiONPs, into primary alginate-modified cellulose (PAC), Gouda et al [74] effectively produced unique self-healing eco-sustainable nano-modified coating. The results from spectroscopy showed that the synthesis of PAC/CuONPs, PAC/Fe 3 O 4 NPs, and PAC/NiONPs with uniform distributions and particulate sizes of 23, 10, and 43 nm, correspondingly, was effective in producing PAC/MONPs nanocomposites.…”
Section: Self-healing-based Nano-modified Coatingmentioning
confidence: 99%